Meloidogyne incognita (Nematoda: Meloidogynidae) sterol-binding protein Mi-SBP-1 as a target for its management. Issue 13 (December 2019) - Shivakumara, Tagginahalli N.; Somvanshi, Vishal Singh; Phani, Victor; Chaudhary, Sonam; Hada, Alkesh; Budhwar, Roli; Shukla, Rohit Nandan; Rao, Uma
Graphical abstract: Highlights: A homolog of Caenorhabditis elegans sterol-binding protein-1 was identified in Meloidogyne incognita . Mi-sbp-1 is a transcriptional regulator of several lipogenesis pathway genes. In-vitro and host-induced RNA interference silencing of Mi-sbp-1 reduced nematode parasitism. Mi-sbp-1 can be used as a target for the management of M. incognita. This approach can be extended to manage other parasitic nematodes. Abstract: Meloidogyne incognita is a polyphagous plant-parasitic nematode that causes considerable yield loss in agricultural and horticultural crops. The management options available for M. incognita are extremely limited. Here we identified and characterised a M. incognita homolog of Caenorhabditis elegans sterol-binding protein (Mi-SBP-1), a transcriptional regulator of several lipogenesis pathway genes, and used RNA interference-mediated gene silencing to establish its utility as a target for the management of M. incognita . Mi-sbp-1 is predicted to be a helix-loop-helix domain containing DNA binding transcription factor, and is present in the M. incognita genome in three copies. The RNA-Seq analysis of Mi-sbp-1 silenced second stage juveniles confirmed the key role of this gene in lipogenesis regulation in M. incognita . In vitro and host-induced gene silencing of Mi-sbp-1 in M. incognita second stage juveniles resulted in loss of nematodes' ability to utilise the stored fat reserves, slower nematode development, and reduced parasitism on adzuki bean and tobacco plants. The multiplication factor for the Mi-sbp-1 silenced nematodes on adzuki bean plants was reduced by 51% compared with the control nematodes in which Mi-sbp-1 was not silenced. Transgenic expression of the double-stranded RNA construct of the Mi-sbp-1 gene in tobacco plants caused 40–45% reduction in M. incognita multiplication, 30–43.8% reduction in the number of egg masses, and 33–54% reduction in the number of eggs per egg mass compared with the wild type control plants. Our results confirm that Mi-sbp-1 is a key regulator of lipogenesis in M. incognita and suggest that it can be used as an effective target for its management. The findings of this study can be extended to develop methods to manage other economically important parasitic nematodes.